Edge/Defect‐Rich, Metallic, and Oxygen‐Heteroatom‐Doped WS2 Superstructure with Superior Electrocatalytic Performance for Green Solar Energy Conversion. Issue 4 (5th February 2019) - Yin, Jie; Wei, Jiazhen; Guo, Junxue; Shi, Shaozhen; Chai, Ning; Zhang, Kaixuan; Xu, Wenli; Yuan, Cang; Liu, Ting; Lin, Weili; Zhang, Qi; Zhou, Huawei; et al.
Abstract: Two‐dimensional tungsten sulfide is widely applied in electrocatalysis. However, WS2 possesses catalytic active sites located at the layer edge and an inert surface for catalysis. Therefore, increasing the exposure of active sites at the edge and effectively activating the inert sites on the surface is an important challenge. Here, an edge/defect‐rich and oxygen‐heteroatom‐doped WS2 (ED‐O‐WS2 ) superstructure was synthesized. The power‐conversion efficiency (PCE) of dye‐sensitized solar cells (DSCs) based on an ED‐O‐WS2 counter electrode reached 10.36 % (under 1 sun, AM 1.5, 100 mW cm −2 ) and 11.19 % (under 40 mW cm −2 ). These values are, to our knowledge, the highest reported efficiency for DSCs based on Pt‐free counter electrodes in I3 − /I − electrolytes. Analysis of the micro/nano structure and the electrocatalytic mechanism indicate that ED‐O‐WS2 exhibits metallic properties in the electrolyte, and that abundant edges and defects as well as oxygen doping in ED‐O‐WS2 play an important role in improving the catalytic activity of WS2 . Moreover, ED‐O‐WS2 displays better catalytic reversibility for I3 − /I − electrolytes than Pt. Abstract : Doped and defective : Increasing the exposure of active sites at the edge and effectively activating the inert sites on the surface of WS2 is an important challenge. An edge/defect‐rich and oxygen‐heteroatom‐doped WS2 (ED‐O‐WS2 ) superstructure is synthesized. The abundant edges and defects as well as the oxygen doping in ED‐O‐WS2 play an important role in improving the catalytic activity of WS2 .